Teeth sizes in their correlation with parameters of dentofacial arches and maxillofacial area based on native cranial preparations examination - D. A. Domenyuk; E. G. Vedeshina; S. V. Dmitrienko (Кубанский научный медицинский вестник, 2016)
The work offers a view on the results obtained from a radiological and morphometric study of native preparations obtained from 43 passported skulls with physiological occlusion and normodontia of permanent teeth under neutral position of the jaws and a neutral type of gnathic facial skull. It was found that in patients with physiological occlusion of permanent teeth, skulls with neutral type of gnathic facial part of the cranium as well as neutral jaw relationships proved to be predominant, while the major parameters of the dentofacial arches are determined through mesial-distal diameters of the teeth.